The impact of alcohol on clinical outcomes in established psychosis: a longitudinal study. (11th June 2014) - Barrowclough, Christine; Eisner, Emily; Bucci, Sandra; Emsley, Richard; Wykes, Til
Abstract Background and Aims Alcohol use disorders are common among people with psychosis and are associated with poorer prognoses. In psychosis patients, there are inconsistent findings regarding the link between alcohol disorders and clinical symptomatic outcomes. This study examined the relationships between alcohol consumption and specific clinical outcomes, including affective symptoms, in psychosis. Methods Participants were recruited from secondary care services in the United Kingdom. Two hundred and ten participants whose substance use met inclusion for an alcohol disorder were compared with other substance users (n = 117) on baseline demographic, clinical and substance use variables. The alcohol subgroup was assessed at three time‐points, with repeated measures of psychopathology and alcohol use over a 2‐year period. Generalized estimating equations (GEE) models were used to examine whether change in alcohol use was associated with change in clinical outcomes. We controlled for a wide range of potential confounds, including other substance use. Results A small but specific effect was evident for change in the quantity of alcohol consumed on change in depression (adjusted coefficient for 10 total units over 90 days: 0.0015, P = 0.047). Alcohol consumption was not associated with subsequent severity of psychotic symptoms (adjusted coefficient for Positive and Negative Syndrome Scale general for 10 average daily units 0.2492, P = 0.420) or severity of anxiety symptoms (adjusted coefficient for 10 average daily units 0.0534, P = 0.473). Conclusions For people with psychosis, the most detrimental effect of alcohol consumption appears to be its effect on mood. Some of this effect seems to be reversible, with drinking reduction associated with subsequent mood improvement.